2014
DOI: 10.1287/orsc.2013.0891
|View full text |Cite
|
Sign up to set email alerts
|

An Image of Who We Might Become: Vision Communication, Possible Selves, and Vision Pursuit

Abstract: We propose a model of vision communication that emphasizes the mediating role of follower collective possible selves—that is, self-conception in terms of what the collective (team, organization) which one is a member of may become in the future that can be held by individuals but can also be shared by multiple individuals. Our model is the first to provide an integrative account of how vision communication may stimulate the pursuit of the vision by individuals and collectives, and it complements and extends pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(168 citation statements)
references
References 128 publications
3
163
0
2
Order By: Relevance
“…Indeed, our findings revealed a positive association between the transformational leadership component "articulating a vision" and commitment to the ideation program and a negative association between "individualized support" and organization-focused idea generation. Our findings support earlier notions that a clear vision and effective communication about it are critical to mobilize and encourage followers to commit themselves to creative endeavors (Mumford, Hunter, Eubanks, Bedell, & Murphy, 2007;Stam, Lord, Van Knippenberg, & Wisse, 2014;Stam, Van Knippenberg, & Wisse, 2010a, 2010bVenus, Stam, & Van Knippenberg, 2013). Commitment in our context was the increased engagement in the organizational ideation program.…”
Section: Theoretical Implicationssupporting
confidence: 86%
“…Indeed, our findings revealed a positive association between the transformational leadership component "articulating a vision" and commitment to the ideation program and a negative association between "individualized support" and organization-focused idea generation. Our findings support earlier notions that a clear vision and effective communication about it are critical to mobilize and encourage followers to commit themselves to creative endeavors (Mumford, Hunter, Eubanks, Bedell, & Murphy, 2007;Stam, Lord, Van Knippenberg, & Wisse, 2014;Stam, Van Knippenberg, & Wisse, 2010a, 2010bVenus, Stam, & Van Knippenberg, 2013). Commitment in our context was the increased engagement in the organizational ideation program.…”
Section: Theoretical Implicationssupporting
confidence: 86%
“…It represents one's knowledge of oneself and it can be seen as the 'output' of a learning process. In a similar vein, Stam et al (2014) argue that the self-concept determines the perception and the knowledge of one's self (p. 1175). They differentiate between the self as we currently experience it and a possible self.…”
Section: Research Gap and Methodsmentioning
confidence: 99%
“…van Knippenberg & Sitkin, 2013). In a recent conceptualization, Stam et al (2014) highlighted the role of a leader's vision communication in forming follower acceptance of the vision of the leader. Another study found individual differences among followers' regulatory focus (Stam, van Knippenberg, & Wisse, 2010).…”
Section: Enhancing Our Understanding Of Vision In Organizations: Towamentioning
confidence: 99%
“…In line with extant work (e.g., Shamir, House, & Arthur, 1993), these processes depend on identification with the collective and motivation to process the vision. Stam et al (2014) emphasized the cognitive processes associating a leader's vision with the actual sharing of the vision by followers. We build on their work by delineating the role of ethical processes in the formation of shared vision and by portraying implications for organizational outcomes.…”
Section: Enhancing Our Understanding Of Vision In Organizations: Towamentioning
confidence: 99%